Pengaruh bahasa Arab dalam kaedah waqaf: kajian terhadap ayat 25, 26 dan 85 dari surah Al-Baqarah - Mohd Hashim, Nurulhuda; Hassan, Abd Rauf (Centre of Quranic Research, University of Malaya, 2013)
Arabic is a language selected as the source language used in the Qur'an. The manners and language accuracy is preserved with the systematic method outlined by a discipline known as Tajwid. Therefore, this study will examine aspects of Arabic linguistics applied by the reader in determining waqaf while reciting the Quran. The objectives of this study are to determine the factors of tendency among respondents when they select a place to do waqaf, analyze the aspects of Arab linguistics applied and to describe the requirements of waqaf in Qur’an recitation. This study employs a qualitative method with samples of seven respondents who have prior knowledge of Arabic. Data is gathered by recording which includes the Quran recitation followed by and interview. Findings of this study show that there are several factors that contribute to the high tendency among respondents to perform waqaf in Qur’an recitation. The most prominent factors are the influence of breathing, existing knowledge of tajwid and the habits of daily reading. In addition, the linguistic aspects of Arabic used in the waqaf are syntax and semantics. In conclusion, the need to apply the knowledge of Arabic language in waqaf is to determine the accuracy of meaning in waqaf in reciting the al-Quran. Therefore, the application of linguistic knowledge in reading Arabic and understanding al-Quran is significant in order to comprehend the contents of al-Qur'an in general and to determine the accuracy of meaning and sentence structure in waqaf in particular.